(untitled) (Indonesian Minority Justice Review, 2025)
This paper offers a comparative analysis of Indonesia’s religious freedom laws and minority rights protections, evaluating their alignment with international standards such as the Universal Declaration of Human Rights and the International Covenant on Civil and Political Rights. While Indonesia’s Constitution guarantees religious freedom, minority religious groups, including the Ahmadiyya, Christians, and indigenous belief systems, face significant restrictions on their practice and recognition. The study examines key legislative frameworks, including the 1965 Blasphemy Law and the 2006 Joint Ministerial Decree on Religious Groups, assessing their impact on religious minorities. The paper contrasts these national laws with international human rights standards, highlighting gaps in Indonesia’s legal framework that lead to the persecution of religious minorities. Using case law, human rights reports, and interviews with legal experts and religious leaders, the paper explores how the Indonesian legal system often fails to protect religious minorities from violence, discrimination, and legal marginalization. The findings suggest that while Indonesia’s laws theoretically uphold religious freedom, practical enforcement and political dynamics often undermine these protections. The paper concludes by recommending legal reforms to bring Indonesia’s laws in line with international human rights standards, including the decriminalization of religious offenses and the establishment of stronger protections for minority religious communities.